A review of domestic research trends of Fischer-Tropsch for the production of light hydrocarbons and middle distillates from syngas - Kim, Jin Ho; Kim, Hyo Sik; Kim, Ji Hyeon; Ryu, Jae Hong; Kang, Suk Hwan; Park, Myung June (Korean Chemical Engineering Research, 2019)
Fischer-Tropsch synthesis process is a typical method for synthesizing hydrocarbons from syngas and is mainly known as iron (Fe) and cobalt (Co) catalysts. Currently, some technologies such as CTL (Coal to Liquid) and GTL (Gas to Liquid) are operated on a commercial scale depending on the products, but the research to produce light hydrocarbons and middle distillates directly has not been commercialized. Therefore, in this study, domestic studies for direct production of light hydrocarbons and middle distillates are summarized and the effect of catalyst preparation, promoter addition, zeolite combination on product selectivity is investigated.
Keywords: Co-based catalyst; Fe-based catalyst; Fischer-tropsch; Light hydrocarbons; Middle distillates; Syngas